Marketing researches of restaurant business as development element of tourism internal market (Journal of Geography and Environmental Management, 2018)
In this article considered and systematized to the feature of the givenservices in accordance by demand of consumers on the enterprises ofpublic food consumption.With this цельюпровели marketing researchesby the method of questionnaire in area of satisfactions of necessities ofconsumers by quality of the rendered services and of long duration relationsbetween restaurants and guests. Except it, description of personnelof restaurant was created, on the basis of psychological aspects, such as,communication of employees inter se and by a guest. On the basis of toresearch work, using the method of questionnaire, by authors on the exampleof restaurant of “Тaу Дaстaрхaн” was certain level of satisfactionof the Kazakhstan consumers. In a percent index, recommendations weresimilarly given for улучению qualities of окозaния services in restaurants.